Pemberdayaan Masyarakat Melalui Pokdarwis Untuk Mengembangkan Desa Wisata Sumberbulu Di Desa Pendem Mojogedang Karanganyar - Laraswati Laraswati; Made Prasta Yostitia Pradipta; Hapsari Wahyuningsih (Sekolah Tinggi Pariwisata Sahid Surakarta, 2021)
Community Empowerment through Pokdarwis to Develop Sumberbulu Tourism Village in Pendem Mojogedang Karanganyar Village the purpose of carrying out this research is to determine the role of Pokdarwis through community empowerment in developing tourist villages and to describe the development and implementation of Pokdarwis through community empowerment in Sumberbulu tourism village. This research is a qualitative research with primary and secondary data sources carried out by means of observation, interview, documentation study, and literature study using data triangulation techniques. The variables used in this study are independent variables consisting of initiators, implementers, and beneficiaries and the dependent variable is the development of a tourism village. The results showed that the role of Pokdarwis through community empowerment was carried out through various outreach and counseling, various discussions, providing information, motivating and organizing activities and training in the tourism sector. Community empowerment is carried out in several stages, namely planning where Pokdarwis is a community forum for conveying ideas and ideas, organizing by Pokdarwis involving the entire community in activities and management of tourism villages, implementation involving the community as the main human resource in implementing activities, and evaluation. Community involvement is expected to provide benefits to the community both economically and socio-culture which have an impact on improving the economic welfare of local communities. The development and implementation of pokdarwis is focused on empowering the community both in terms of the quality of human resources, and in terms of marketing that will be involved in every tourism village activity.